A Home-made Vidicon Digitizer for Ultra-Fast Experiments in the Nanosecond Time-Scale - Marcel Gremaud; Paul-Hervé Chassot; Paul Suppan (CHIMIA)
A commercial vidicon TV camera can be adapted to digitize the trace from the screen of a storage oscilloscope, with a resolution of up to 9 x 9 bits. With fast storage oscilloscopes this technique is used to digitize and to plot kinetic information in the nanosecond time scale at a fraction of the costs of direct digitizers.